Synergistic Effect of Multi-field Force on Condensable Particulate Matter Properties and Behavior in Flue Gas: A Case Study in a Municipal Solid Waste Incineration Plant - Wenting Liu; Bowen Zhao; Qian Feng; Zhiyong Zhou; Jianyi Lu (Aerosol and Air Quality Research)
Abstract At present, filterable particulate matter (FPM) emissions from stable source flue gases are well controlled, and the more difficult to remove condensable particulate matter (CPM) has received much attention due to its environmental hazards. In this study, we built a cold electrode electrostatic precipitator (CE-ESP) and systematically investigated the removal efficiency of CPM from municipal solid waste incineration plant flue gas by CE-ESP under three different operating modes. The results showed that hydrocarbons, esters and aromatic compounds were the main organic substances in CPM. The CE-ESP had a significant contribution to the removal of SO42−, F−, Al, Ni, Cr, and Pb from CPM. In contrast, it had a less effective removal of NO3 − and Ca in CPM. The CE-ESP was effective for removing esters in CPM. The removal efficiency of CE-ESP for CPM could reach 76%, and the removal efficiency of organic substance was higher than that of inorganic substance. It is demonstrated that the combination of thermophoretic force and electric field in CE-ESP intensifies the turbulent agglomeration process, and the diffusion force generated by the concentration field synergistically enhances the interparticle coagulation and agglomeration. This promotes the homogeneous condensation process of CPM and the heterogeneous condensation of CPM and FPM, which is conducive to the reduction of condensable particulate matter in flue gas and can provide a theoretical basis for practical application in engineering.